WAYS OF NEOLOGISM FORMATION IN ENGLISH - Khasanova , Maftuna Sherali qizi (Innovative Development in Educational Activities, 2023)
The article deals with the formation of neologisms in the modern. New words have been entering English at an ever increasing rate. Although this phenomenon is often associated with new things, processes, and concepts that need names, there is also a great increase, indeed acceleration, in clever, trendy, eye-ear-catching words.